Implementasi Program Sekolah Sehat Berkarakter di SD Muhammadiyah Condongcatur - Hestiningtyas, Ririn; Saifudin, Muhamad Fakhrur (Universitas Negeri Surabaya, 2021)
The purpose of this study is to describe the implementation of the character healthy school program as well as the supporting and inhibiting factors in its implementation at SD Muhammadiyah Condongcatur. The approach used in this study is a descriptive qualitative approach. Data collection methods used are interviews, observation, and documentation. The result of the research is that SD Muhammadiyah Condongcatur implements a character healthy school program that is in accordance with the national standard guidelines for implementing a healthy school with character, namely approaches, strategies, and procedures. SD Muhammadiyah Condongcatur seeks to cultivate PHBS by integrating the main characters, namely religious, nationalist, independent, mutual cooperation, and integrity. Supporting factors are UKS/M Ibnu Sina at SD Muhammadiyah Condongcatur which has facilities and services of national standard, canteen at SD Muhammadiyah Condongcatur which already has a BPOM certificate, collaboration with experienced outsiders, and has excellent work programs. The inhibiting factors for the implementation of the integrity character values that have not been implemented properly, the density of classes that are still not in accordance with the standards of a healthy school with character, the lack of cleanliness of student toilets.